PTH-027 Review of faults and usage of two upper and lower gastrointestinal endoscopes suppliers in nhs lothian over a 40 month period. (22nd June 2015) - Inglis, S; Kennedy, N; Plevris, JN
Abstract : Introduction: Endoscopes are used for diagnostic and therapeutic applications in Gastroenterology (GI). The nature of these procedures, can subject endoscopes to hard use and stringent cleaning and decontamination procedures, leading to numerous faults developing over their lifespan. The aim was to review the service history of two upper and lower GI endoscopes suppliers within NHS Lothian, and usage, over a 40 month period. Method: The service history of each GI endoscope owned by NHS Lothian was requested from each supplier's service department, between January 2011 and April 2014. Usage data for each endoscope with a repair was extracted from the Endoscopy Reporting System (Unisoft). Each repair was reviewed and classified as either an angulation, damage, leak, blockage, image, electrical, or other fault. The fault and corresponding usage was split by type and supplier to calculate average number of repairs, usage and give a measure of reliability (average repairs per annum/average procedure per annum). A chi square was performed to see if there were significant differences between fault categories from each supplier. A p < 0.05 was classed as significant. Results: The results obtained from the analysis of the faults from supplier A and supplier B were: Angulation 2 and 4.4% (p = 0.10), Damage 9.3 and 6% (p = 0.15), Blockages 17.7 and 20% (p = 0.49), Image faults 21 and 29.6% (p = 0.02), Leaks 40.7 and 22.4 % (p < 0.001), electrical failures 3.7 and 13.2% (p < 0.001) and other of 5.7 and 4.4% (p = 0.50) respectively. A summary of the number of scopes, procedures and repairs from both suppliers are shown in Table 1 . Conclusion: A comprehensive registry of endoscopes with individual repair profiles can give extremely valuable information regarding endoscope reliability and durability. This ensures that hardware quality is maintained. It can facilitate the replacement process as well as help in the negotiation of maintenance contracts. Modern endoscopes in general are of similar high quality and have similar repair profiles. There are individual company differences in terms of vulnerable parts for different scopes but in general choice of endoscopes should be based on existing facilities, unit case mix and cost rather than on individual brand names. Disclosure of interest: S. Inglis: None Declared, N. Kennedy: None Declared, J. Plevris Grant/ Research Support from: JN Plevris has received funding from Fujifilm in the past for endoscopic research.